2017
DOI: 10.18632/oncotarget.23795
|View full text |Cite
|
Sign up to set email alerts
|

Preclinical assessment of galunisertib (LY2157299 monohydrate), a first-in-class transforming growth factor-β receptor type I inhibitor

Abstract: Transforming growth factor-β (TGFβ) is an important driver of tumor growth via intrinsic and extrinsic mechanisms, and is therefore an attractive target for developing cancer therapeutics. Using preclinical models, we characterized the anti-tumor activity of a small molecule inhibitor of TGFβ receptor I (TGFβRI), galunisertib (LY2157299 monohydrate). Galunisertib demonstrated potent and selective inhibition of TGFβRI with corresponding inhibition of downstream signaling via inhibition of SMAD phosphorylation (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
89
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 125 publications
(98 citation statements)
references
References 43 publications
3
89
0
1
Order By: Relevance
“…Galunisertib (LY2157299) is a small molecule that selectively inhibits the serine/threonine kinase of the TGF‐β receptor type I (TGF‐β RI/ALK5) . Galunisertib had an acceptable safety profile in phase 1 studies and may be well tolerated in patients with HCC .…”
Section: Introductionmentioning
confidence: 99%
“…Galunisertib (LY2157299) is a small molecule that selectively inhibits the serine/threonine kinase of the TGF‐β receptor type I (TGF‐β RI/ALK5) . Galunisertib had an acceptable safety profile in phase 1 studies and may be well tolerated in patients with HCC .…”
Section: Introductionmentioning
confidence: 99%
“…Our results suggested that cESRP1 effectively increases the abundance of Smad7/p21 (CDKN1A) and formed a double-negative feedback loop to abolish the effect of the TGF-β/Smad signalling pathway. A growing number of clinical studies have shown that anti-TGF-β therapy has an acceptable safety/tolerability profile and exhibits anti-tumour activity in subsets of patients [70][71][72]. In this study, we used an SCLC chemoresistant cell line orthotopic xenograft model and observed that the TGF-β signalling inhibitor LY2157299 (galunisertib), which was bioavailable, effectively suppressed the TGF-β signalling pathway, augmenting tumour chemotherapy responsiveness in combination with chemotherapeutic drugs.…”
Section: Discussionmentioning
confidence: 95%
“…TGFβ is an attractive therapeutic target for enhancing the effects of chemotherapy and immune therapy. Multiple therapeutic strategies targeting the TGFβ pathway are undergoing clinical studies in different cancers including PDA (de Gramont et al , ; Yingling et al , ). Our study underscores the importance of stratifying the patients in these studies such that those with tumor cell mutations in TGFβ signaling would be candidates for inhibition of stromal TGFβ signaling in combination with standard or immune therapy.…”
Section: Discussionmentioning
confidence: 99%